(untitled) (World Bulletin of Management and Law, 2023)
In this article, research was conducted on the conduct of court proceedings of international investment arbitration, the procedure for the resolution of disputes and the application of sanctions within the scope of competence, as well as the manner in which this jurisdiction is exercised and accepted. Also, the similarities and differences between the scientific theory of international investment arbitration and the practical rules used in real life are considered on the example of practical international disputes, and based on the researches of world scientists, scientific works, statistics of the international arbitration court , current problems are discussed. Personal suggestions have been developed that can be a practical solution.